Role of n-alkoxy terminal end groups on mesomorphism. (2nd July 2016) - Muniya, N. R.; Patel, V. R.
ABSTRACT: A homologous series RO-C6 H4 -CH:CH-COO-C6 H4 -CO-CH:CH-C6 H4 -OC6 H13 (n) of novel liquid crystals (LC) has been synthesized and studied with a view to understanding and establishing the relation between molecular structure of a substance and the LC properties or behavior of thermotropic LC materials. Novel series consist of 11 homologues. C1 and C2 homologue derivatives are non-LCs and the rest of homologues (C3 to C16 ) are nematogenic without exhibition of smectic property. Transition temperatures were determined by an optical polarizing microscopy equipped with a heating stage. Transition curve Cr-N/I of a phase diagram behaved in normal manner. N/I transition curve partly deviated at C6 and C10 homologues from normal descending behavior, and exhibited very narrow and sharp odd-even effects. Textures of nematic phase are threaded or Schlieren. Thermal, analytical, and spectral data confirmed the molecular structures of novel chalconyl ester derivatives. Thermal stability for nematic is 95.77°C and the upper and lower mesophase lengths vary from 35 to 16°C at C5 and C8 homologues respectively. Group efficiency order derived for nematic on the basis thermal stability is -OC10 H21 (n) > -OC8 H17 (n) > -OC6 H13 (n).